Electrochemically Mediated Surface-Initiated Atom Transfer Radical Polymerization by ppm of CuII/Tris(2-pyridylmethyl)amine - Guo, Tingting (Langmuir : the ACS journal of surfaces and colloids, 2024)
Atom transfer radical polymerization (ATRP) is one of the most widely used methods for modifying surfaces with functional polymer films and has received considerable attention in recent years. Here, we report an electrochemically mediated surface-initiated ATRP to graft polymer brushes onto solid substrates catalyzed by ppm amounts of CuII/TPMA in water/MeOH solution. We systematically investigated the type and concentrations of copper/ligand and applied potentials correlated to the polymerization kinetics and polymer brush thickness. Gradient polymer brushes and various types of polymer brushes are prepared. Block copolymerization of 2-hydroxyethyl methacrylate (HEMA) and 3-sulfopropyl methacrylate potassium salt (PSPMA) (poly(HEMA-b-SPMA)) with ultralow ppm eATRP indicates the remarkable preservation of chain end functionality and a pronounced "living" characteristic feature of ppm-level eATRP in aqueous solution for surface polymerization